Pengaruh Kepemimpinan Transformasional Perempuan terhadap Loyalitas Organisasi KOPRI Pergerakan Mahasiswa Islam Indonesia DKI Jakarta - Nanda Asifa Putri; Osly Usman (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the influence of women's transformational leadership on organizational loyalty among members of KOPRI PMII DKI Jakarta. The research employed a quantitative approach using a survey method involving 100 active members of KOPRI PMII DKI Jakarta selected through purposive sampling. The transformational leadership variable was measured through the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, while organizational loyalty was assessed through commitment, obedience, dedication, and willingness to sacrifice. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression using SPSS. The findings indicate that women's transformational leadership has a positive and significant effect on organizational loyalty, with a significance value of 0.033 (< 0.05). Furthermore, all dimensions of transformational leadership and organizational loyalty were categorized as high. These findings suggest that female leadership characterized by role modeling, motivation, individualized consideration, and member empowerment can enhance organizational loyalty among cadres. This study highlights the importance of strengthening women's transformational leadership capacity as a strategic effort to improve member loyalty and sustain women's cadre-based organizations.